Utilisation of Canva Application and Student Worksheet Digital-based Islamic learning - Amalia, Frizka; Salahuddin, Rahmad; Astutik, Anita Puji (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to describe how PAI teachers use the Canva application media and sheets student work in learning digital-based, as well as illustrate student learning conditions when the teacher uses the Canva application and worksheets in digital-based PAI learning. Study This implemented at SMP Muhammadiyah 1 Sidoarjo. This study uses a qualitative descriptive approach that ensures data through data validity. Technique research data was collected through interviews, documents, and observations with subject study PAI teachers and class VII students. Data were collected for data reduction for the next in the analysis using the data triangulation technique for making conclusions and interrogation. The research results explain that the application canvas and worksheets used in PAI learning using the Flipped classroom model assist PAI teachers in explaining material learning effectively and efficiently. The Canva application is used to provide understanding to students through mind mapping, and the worksheet application, as student worksheets, is used to evaluate learning. By utilizing these two learning media, it turns out that it is able to improve student learning conditions that are active, innovative, creative, effective, and fun. Active students can be seen from the involvement of students in answering the question and answer questions, innovative is shown through the results of mind mapping work, practical can be seen from the achievement of understanding as measured from the table worksheet, and fun can be seen from the learning conditions of students in responding to learning.